Beeldhouwers in Limburg. - Stadhuis, Heerlen (Heerlen : Gemeentebestuur, 1978)
Carlier, Frans ; Cox, Carla ; Devens, Dré ; Houben, Jean ; Knippenbergh, Mathieu ; Lendfers, Twan ; Muré, Marie-José ; Reijnen, Louis ; Schuijren, Peter ; Siebelt, Ben ; van Wetering, Han ; van Wijk, Dick ; Willems, Lex ; Wishaupt, Jef
Beeldhouwers in Limburg, Stadhuis, Heerlen, oktober/november 1978
boek
Keywords: Nederland; Limburg